Depth Defect Analysis of BaO Thin Films Doped with Cd Via Positron Annihilation Techniques - Dahamni, Mohamed El Amine; Hamzaoui, Nassima; Ghamnia, Mostefa; Yener, Murat Yavuz; Yumak, Ayşe; Tav, Cumali; Yahşi, Uğur (Taylor & Francis, 2026)
Thin films of pure and cadmium-doped barium oxide (BaO) with 2, 4, and 6 wt% Cd were made using the spin-coating method and placed on glass at 450°C. Atomic force microscopy (AFM) revealed coarse, textured surfaces with BaO crystallites ranging from 1.4 to 150 nm in size, depending on the Cd concentration. Optical properties were investigated using UV–visible spectroscopy, revealing high transparency and direct bandgap energies between 3.467 and 3.728 eV. Defects were studied using Doppler broadening spectroscopy (DBS), which showed that there were different types of defects linked to oxygen and barium. A correlation was observed between the S parameter of DBS, crystallite size, and optical bandgap. Additionally, positron annihilation lifetime spectroscopy (PALS) was used to study vacancy-type defects and verify the positron lifetimes connected to the S parameter. The results demonstrate that Cd doping significantly influences the microstructure, defect landscape, and optoelectronic properties of BaO thin films.
Keywords: BaO; Vacancy Defects; Oxygen and Barium Defects; Doppler Broadening Spectroscopy; Positron Annihilation Lifetime Spectroscopy